PEMBANGUNAN HUKUM PERLINDUNGAN KONSUMEN BERORIENTASI EKOSENTRISME TERKAIT AKTIVITAS GREENWASHING INDUSTRI AMDK - Gaol, Heru Saputra Lumban; Rini, Wafia Silvi Dhesinta (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
Based on a study in the Journal Nature, it is known that 86% of plastic waste in the ocean comes from Asian rivers. Indonesia was reported to be the second highest level country of waste production, producing more than 3 million metric tons of plastic waste every year. Generally, the waste comes from the industrial sector, especially Bottled Drinking Water (AMDK). Starting from collective concern about global environmental issues, comes behavior to encourage sustainable consumption and production. Nowadays, consumers are more inclined to choose eco-friendly products or services. Unfortunately, this consumer awareness is also accompanied by greenwashing conducted by business actors as biased information related to products. This greenwashing practice certainly contradicts consumers' basic rights as stipulated in Article 4 point 3 of the Consumer Protection Law regarding consumer right to get correct, clear, and honest information of goods and/or services. This research examined the framework for developing consumer protection laws that can protect consumers from the negative excesses of greenwashing in the AMDK industry. To analyze the problem, socio-legal research methods which use a legal and social science approach. The research results show that consumers already have environmental awareness of AMDK products and are also willing to buy ecolabel products even if the price is more expensive. To protect these interests, it is necessary to build an ecocentrism-oriented legal development framework that prioritizes the role of both parties in sustainable production and consumption behavior.